Assessment of variability, heritable components and grouping of Indian rose - PANWAR, SAPNA; SINGH, KANWAR PAL; NAMITA, NAMITA (The Indian Journal of Agricultural Sciences, 2012)
Thirty-two genotypes of rose were evaluated for various vegetative and floral traits to ascertain genetic parameters such as variability, heritability, genetic (GCV) and phenotypic (PCV) coefficient of variation and genetic advance. Further, these genotypes were grouped into five categories, i e plant growth type, flower type, flower diameter, number of colours on inner side of petal and flower colour group on basis of DUS (Distinctness, Uniformity and Stability) guidelines. Analysis of variance for all traits showed highly significant differences among genotypes for all the vegetative and floral traits studied. Phenotypic coefficient of variation (PCV) for all traits was higher than the genotypic coefficient of variation (GCV). High estimates of PCV and GCV were observed for weight per flower, number of petals per flower, number of flowers per plant and prickle density. Moreover, high heritability (>80%) were noticed for plant height, internodal length, neck length, flower diameter, weight per flower, number of petals per flower and number of flowers per plant. High genetic advance was observed for weight per flower followed by number of petals per flower and number of flowers per plant. High coefficient of variation both at the genotypic and phenotypic level along with high heritability and genetic advance was observed for weight per flower, number of petals per flower and number of flowers per plant. The diverse genotypes with peculiar characteristics, identified in the present study may be used as parents in the crop improvement programme for evolving elite genotypes.